2019
DOI: 10.1039/c9ra00091g
|View full text |Cite|
|
Sign up to set email alerts
|

Large-scale and fast synthesis of nano-hydroxyapatite powder by a microwave-hydrothermal method

Abstract: The obtained nano-HAP still has high crystallinity, uniform size and good dispersibility when the concentration of Na2HPO4 is 0.4 mol L−1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 37 publications
(28 reference statements)
0
15
0
Order By: Relevance
“…, [7] ), spray cooling [8] , film coating [9] , [10] , preparation of micro- and/or nano-sized powder ( e.g. , [11] ), air purification [12] , [13] , [14] , [15] , medical applications ( e.g. , [16] , [17] , [18] ), and applications utilizing sonochemical reactions/reactors associated with cavitation ( e.g.…”
Section: Introductionmentioning
confidence: 99%
“…, [7] ), spray cooling [8] , film coating [9] , [10] , preparation of micro- and/or nano-sized powder ( e.g. , [11] ), air purification [12] , [13] , [14] , [15] , medical applications ( e.g. , [16] , [17] , [18] ), and applications utilizing sonochemical reactions/reactors associated with cavitation ( e.g.…”
Section: Introductionmentioning
confidence: 99%
“…where V 112/300 is the intensity of the hollow between ( 112) and (300) planes and I 300 is the intensity of the (300) plane. 24,30 In parallel with the qualitative analysis, the production yield was calculated to assess the efficacy with respect to the theoretical yield from the stoichiometrically balanced reaction scheme. This is very important from the industrial perspective, where any probable inverse relationship between quality and yield should be minimal.…”
Section: Powder Characterizationmentioning
confidence: 99%
“…There are several attempts reported in the literature to produce HAp in large scales. Cai et al 24 demonstrated the efficacy of a microwave-based hydrothermal method to accelerate HAp powder production on a large scale. It was observed that with the reaction temperature and time of 160 • C and 40 min, respectively, .4 mol L −1 concentration of Na 2 HPO 4 , 12H 2 O maximized the yield of nano-HAP powder (.033 kg L −1 ).…”
Section: Introductionmentioning
confidence: 99%
“…dextran, CS, alginate, gelatin, carboxymethyl cellulose) [5], CS is known to form an excellent composite with HAp due to their reconcilable properties such as biocompatibility, biodegradability [5], chelation, and adsorption properties [6]. Several methods for synthesizing HAp and CS such as the green method [7][8][9][10] and chemical method [11][12][13][14] have been reported in the literature. The majority of these studies are focused on the influence of synthesis routes and precursors on the biological and physicochemical properties of HAp and CS, such as thermal stability [15,16], and solubility [17,18], crystallinity [19,20], and hardness [21,22].…”
Section: Introductionmentioning
confidence: 99%